Efficacy comparison of different external traditional Chinese medicine therapies as monotherapy or in combination for premenstrual syndrome: a systematic review and network meta-analysis - Xie, Yuhong; Zhao, Jinying; Fan, Shuai; Yang, Ning; Liu, Huiying; Guo, Yuwei; Feng, Xu; Wang, Ziheng; Zhang, Min; Wang, Fuchun (Frontiers in Psychiatry, 2026)
BackgroundPremenstrual syndrome (PMS) is a common gynecological problem that can seriously impair the quality of life of women of childbearing age. Substantial evidence confirms the efficacy of external Traditional Chinese Medicine (TCM) therapies for PMS, though the optimal intervention remains uncertain.ObjectiveThis study aims to compare the efficacy and safety of external TCM therapies for PMS using Bayesian network meta-analysis, thereby informing evidence-based clinical decisions.MethodsWe systematically searched eight databases for randomized controlled trials (RCTs) evaluating various external TCM therapies for PMS, with all searches conducted through March 10, 2025. The primary outcome measures were overall effective rate and symptom severity scores. We used Stata 17.0 to perform network meta-analysis and compare the therapeutic effects of different interventions on improving PMS symptoms.ResultsThe screening process identified 21 eligible RCTs involving 1,818 patients. Most studies demonstrated unclear risk of bias due to insufficient selective reporting details, while six studies were rated high risk for inadequate randomization reporting. The NMA results show that in terms of total effective rate, Jianpi-Shugan acupuncture has the highest SUCRA value (95.7), and for symptom and sign scores, ear acupressure ranks first (SUCRA = 71.2).ConclusionExternal treatment methods of traditional Chinese medicine can serve as a complementary or alternative therapy for PMS; Jianpi-Shugan acupuncture can better enhance the overall effective rate in treating PMS, while ear acupressure is more effective in improving symptom and sign scores. Overall, external treatment methods of TCM for PMS are effective and have almost no side effects, but many high-quality studies are still needed to provide more direct evidence.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025643025.